Diagnostic efficacy of quantitative endoscopic ultrasound elastography for differentiating pancreatic disease. Issue 5 (27th April 2017) - Kim, Su Young; Cho, Jae Hee; Kim, Yoon Jae; Kim, Eui Joo; Park, Ji Young; Jeon, Tae Joo; Kim, Yeon Suk
Abstract: Background and Aim: Endoscopic ultrasound elastography (EUS‐EG) constitutes a novel imaging procedure that allows for the quantification of tissue stiffness with high degrees of accuracy in pancreatic disease. However, the optimal cut‐off and reference strain ratio (SR) value of quantitative EUS‐EG for differential diagnosis in patients with pancreatic disease remains unclear. This study aimed to clarify these values of normal pancreas, chronic pancreatitis, or pancreatic cancer in an Asian population. Methods: Between December 2014 and November 2015, 398 patients without pancreatic disease, 67 patients with chronic pancreatitis, and 90 patients with pancreatic cancer who underwent EUS were enrolled prospectively. Elastographic evaluation was measured using the quotient B/A (SR value). Results: The mean SR was 3.78 ± 1.35 for normal pancreas, 8.21 ± 5.16 for chronic pancreatitis, and 21.80 ± 12.23 for pancreatic cancer ( P  < 0.001). The median SR was 15.14 for mass‐forming pancreatitis and 18.00 for pancreatic cancer ( P  = 0.024). The sensitivity, specificity, and accuracy of the SR were 71.6%, 75.2%, and 74.8%, respectively, for detecting chronic pancreatitis using a cut‐off value of 5.62, and were 95.6%, 96.3%, and 96.2%, respectively, for detecting pancreatic cancer using a cut‐off value of 8.86. Conclusions: We provided reference range SR values for normal pancreas, chronic pancreatitis, and pancreatic cancer, as well as an optimal cut‐off value for chronic pancreatitis and pancreatic cancer diagnostic accuracy in an Asian population. Quantitative EUS‐EG is a supplementary diagnostic method for identifying pancreatic disease.